Diversification strategy and internationalization: Implications for mne performance - Geringer, J. Michael; Beamish, Paul W.; Dacosta, Richard C. (Strategic Management Journal, 1989)
Abstract This study examines potential explanations for performance differences among multinational enterprises (MNEs). The research variables, diversification strategy and degree of internationalization, involve basic elements of firms' strategy: range and relatedness of products, and relative emphasis on foreign versus domestic operations. The sample included the 100 largest MNEs from the U.S. and Europe. Diversification strategy was significantly related to MNE performance, extending Rumelt's seminal research to international business. Degree of internationalization was also significantly related to MNE performance.